Diagnosis of channelopathies affects quality of life and psychological status in patients and relatives. (3rd October 2022) - Berne, P; Usai, F; Silva, E; Onida, A; Melis, I; Casu, G
Abstract: Background: Cardiac channelopathies are a group of inherited cardiovascular diseases with increased risk of sudden cardiac death in structurally normal hearts. The psychological status after their diagnosis has not been thoroughly studied. Purpose: To establish health-related quality of life (QOL) and emotional response to the diagnosis of channelopathies in a cohort of patients and their families. Methods: Adult patients with diagnosis of channelopathies and their relatives were eligible. After enrolment they were divided in 3 groups, according to the time of psychological evaluation: At diagnosis (T0), one year (T1), and 2 years after diagnosis (T2). Psychological evaluation was conducted through self-report questionnaires on QOL (SF-12), general anxiety (BAI), depression (BDI-II), perceived stress (PSS-10), post-traumatic stress (IES-R), and protective resilience resources (RSA). Results: From August 2020 to April 2021, 64 patients (95% Brugada syndrome, 3% long QT syndrome, and 2% catecholaminergic polymorphic ventricular tachycardia) and 41 relatives were enrolled. A control group of 105 healthy subjects, matched to the study group regarding age, gender and level of education, was also enrolled. Patients at T0 showed increased physical and reduced mental QOL; at T1, reduction of RSA; and at T2, reduction of RSA and increased BAI. A significant percentage of patients referred the occurrence of a traumatic event during their lifetime at T0, T1 and T2 (Figure 1). At T0 relatives presented high PSS-10 and a high proportion of them reported experiencing a traumatic episode during their lifetime. BAI score was high among relatives at T0, T1 and T2, reaching levels of concern 2 years after the diagnosis (Figure 2). Female gender independently predicted MCS-12 in patients at T0. Conclusions: Diagnosis of channelopathies impact different areas of QOL and the psychological sphere in patients (QOL, resilience, anxiety and occurrence of traumatic events during lifetime) and relatives (anxiety, stress, and occurrence of traumatic events during lifetime), and at different moments after the diagnosis. Female gender was an independent predictor of worse mental QOL in patients at T0. Patients and their families should be involved in psychological counselling and psychoeducational interventions, taking into account their differences and the timing of psychological responses, in order to better support them in adjusting to their new life circumstances. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Regione Autonoma della Sardegna